Future Prospects for Assessment of General Movements in Developing Countries - Zhussupova, Zhanna; Ayaganov, Dinmukhamed; Zharmakhanova, Gulmira; Mamedbayli, Ayten (West Kazakhstan Medical Journal, 2023)
The well-being of children is crucial for a nation’s demographic, economic, and intellectual prospects. Developing countries face an increasing number of children with disabilities, primarily attributed to congenital developmental defects, neurological disorders, and other health issues. Neurological disorders pose significant challenges to realizing the full potential of children and society. Early intervention is essential for improving functional outcomes in infants with neurological impairments. General Movements (GM) assessment, a predictor of subsequent neurological outcomes, plays a vital role in early detection. However, its widespread implementation in developing countries is limited. This article explores the history of GM assessment, its current state in developing countries, and the potential for mobile applications to revolutionize early assessments and interventions in developing countries.